Fracture mechanism and failure strain of TA31 titanium alloy for deep-sea pressure hulls based on continuum damage mechanics - Zhang, Bowen; Wan, Zhengquan (Frontiers in Materials, 2023)
Titanium alloys have high fatigue resistance, high corrosion resistance, high-temperature resistance, and other excellent properties, and have been widely used in deep-sea equipment and aviation industries. In this paper, the fracture mechanism and failure strain of TA31 titanium alloy, which has been widely used in deep-sea equipment, were studied experimentally and numerically in different stress states. Considering the pressure sensitivity, the Modified Johnson-Cook (MJC) model and the Bonora damage model were used to study the fracture behavior. To obtain the parameters of models, four types of specimens under different stress triaxiality were conducted, and a hybrid experimental-numerical approach was employed in this paper. Then, the coupled constitutive elastic–plastic-damage model was developed and implemented in ABAQUS explicit finite element analysis (FEA) code. Finally, FEA simulation was carried out and compared with the experimental results to validate the suggested model. The comparison revealed that the Bonora model with constant parameters was not enough to predict the failure strain. The damage parameters were sensitive to stress triaxiality. In addition, the fracture morphology was observed by scanning electron microscope (SEM), which revealed the micro-mechanism of failure for TA31 titanium alloy. It is concluded that a higher stress triaxiality and shear mechanism lead to lower plastic deformation, and will inhibit the void growth on the damage evolution.